2014
DOI: 10.1152/jn.00129.2013
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of age-related changes in synaptic transmission onto F344 rat basal forebrain cholinergic neurons using a reduced synaptic preparation

Abstract: Basal forebrain (BF) cholinergic neurons participate in a number of cognitive processes that become impaired during aging. We previously found that age-related enhancement of Ca(2+) buffering in rat cholinergic BF neurons was associated with impaired performance in the water maze spatial learning task (Murchison D, McDermott AN, Lasarge CL, Peebles KA, Bizon JL, and Griffith WH. J Neurophysiol 102: 2194-2207, 2009). One way that altered Ca(2+) buffering could contribute to cognitive impairment involves synapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 114 publications
1
27
0
Order By: Relevance
“…The observation that a contralateral deficit impaired performance on the OPPA task, which requires flexibility in selecting the correct object based on spatial location, but not the control tasks, is interesting in the context of aging and disease. The PER (Burke, Ryan, and Barnes, 2012c; Khan, Liu, Provenzano, Berman, Profaci, Sloan, et al, 2014; Reagh, Ho, Leal, Noche, Chun, Murray, et al, 2015; Ryan, Cardoza, Barense, Kawa, Wallentin-Flores, Arnold, et al, 2012) and mPFC (Griffith, Dubois, Fincher, Peebles, Bizon, and Murchison, 2014; Morrison and Baxter, 2012) are among the most vulnerable brain regions to age-related dysfunction. Even when these areas are compromised, however, aged animals are still able to perform object discriminations and differentiate the left from right side (Beas et al, 2013; Burke, Wallace, Hartzell, Nematollahi, Plange, and Barnes, 2011; Hernandez et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The observation that a contralateral deficit impaired performance on the OPPA task, which requires flexibility in selecting the correct object based on spatial location, but not the control tasks, is interesting in the context of aging and disease. The PER (Burke, Ryan, and Barnes, 2012c; Khan, Liu, Provenzano, Berman, Profaci, Sloan, et al, 2014; Reagh, Ho, Leal, Noche, Chun, Murray, et al, 2015; Ryan, Cardoza, Barense, Kawa, Wallentin-Flores, Arnold, et al, 2012) and mPFC (Griffith, Dubois, Fincher, Peebles, Bizon, and Murchison, 2014; Morrison and Baxter, 2012) are among the most vulnerable brain regions to age-related dysfunction. Even when these areas are compromised, however, aged animals are still able to perform object discriminations and differentiate the left from right side (Beas et al, 2013; Burke, Wallace, Hartzell, Nematollahi, Plange, and Barnes, 2011; Hernandez et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…2C, bottom). Although BF neurons receive both excitatory and inhibitory inputs, BF synaptic transmission is dominated by GABAergic IPSCs as reported previously (Griffith, Dubois et al 2014). In these experiments, approximately 90% of all synaptic transmission was GABA A R-mediated.…”
Section: Resultsmentioning
confidence: 55%
“…To isolate GABA A R-mediated postsynaptic currents, D(−)2-amino-5-phosphonovaleric acid (APV, 40 µM, Sigma) and 6,7-dinitroquinoxaline-2,3-dione (DNQX, 10 µM, Sigma) were added to the perfusion solution. Spontaneous synaptic currents were analyzed using MiniAnalysis 6.0.3 (Synaptosoft) as described previously (DuBois, Parrish et al 2004, DuBois, Damborsky et al 2013, Wang, Dubois et al 2013, Griffith, Dubois et al 2014). Analysis of the electrophysiological data was conducted blind with respect to treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Dietary DHA is also know to modulate a number of neurotransmitter systems including the cholinergic system [ 25 ], which is known to play a key role in memory and learning [ 26 ] and the degradation of which is associated with the typical cognitive deficits observed in normal and pathological aging [ 27 , 28 ]. One group of researchers also demonstrated a role for cholinergic neurotransmission in the regulation of the neurovascular coupling of brain activity and local cerebral blood flow in aged monkeys [ 29 ], and subsequently demonstrated that the age-impaired regional cerebral blood flow (rCBF) response to tactile stimulation was positively modulated following four weeks’ dietary supplementation with 150 mg/kg/day DHA [ 30 ].…”
Section: Introductionmentioning
confidence: 99%